2013
DOI: 10.1161/atvbaha.112.301172
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Impairment of the Vascular Endothelium

Abstract: Objective— Dystrophin, the missing or defective protein in Duchenne muscular dystrophy, is expressed not only in muscle cells but also in vascular endothelial cells (ECs). In this study, we assessed the effects of dystrophin deficiency on the angiogenic capacities of ECs. Approach and Results— We isolated vascular ECs from mdx mice, the murine equivalent of Duchenne muscular dystrophy in humans, and wild-type c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Since reduced capillarity in muscles from mdx mice was previously described as a result of necrosis-induced muscle ischemia (Palladino et al, 2013), we then counted the number of capillaries in GA muscles from C20-treated and untreated mdx mice. In line with the observation of boosted regeneration, the number of capillaries was higher in muscle derived from C20-treated than in muscle derived from vehicle-treated mdx mice, and was similar to that counted in GA muscles from age-matched WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since reduced capillarity in muscles from mdx mice was previously described as a result of necrosis-induced muscle ischemia (Palladino et al, 2013), we then counted the number of capillaries in GA muscles from C20-treated and untreated mdx mice. In line with the observation of boosted regeneration, the number of capillaries was higher in muscle derived from C20-treated than in muscle derived from vehicle-treated mdx mice, and was similar to that counted in GA muscles from age-matched WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another report shows that angiogenesis is impaired in mdx mice, not only in muscle, but systemically, which was proven by laser Doppler perfusion imaging in the hind limb ischemic model, VEGF induced neovascularization quantification in the corneal model, Matrigel subcutaneous angiogenic assay, and quantification of tumor growth and vascularization in the tumor implant model (Palladino et al, 2013). …”
Section: Evidence For Vasculature Changes In Dmdmentioning
confidence: 92%
“…Studies of blood perfusion in mdx mice indicate age or disease progression may have a major effect in vascular changes. A study with 2-month-old mdx mice showed increased blood flow compared to the wild type control in the hindlimb ischemia model, whereas older mice of 6 months showed decreased blood flow (Straino et al, 2004; Palladino et al, 2013). In wild type mice, it has been indicated that aged mice have a reduced response to angiogenesis after ischemia (Palladino et al, 2011, 2012).…”
Section: Evidence For Vasculature Changes In Dmdmentioning
confidence: 99%
“…Also unknown is if functional ischemia manifests primarily as maldistribution of blood flow within the active muscles or as reduced total muscle blood flow. Compensatory mechanisms such as angiogenesis that are engaged to counteract muscle ischemia appear to be robust in young mdx mice (Straino et al, 2004), but impaired in older mdx mice (Palladino et al, 2013), suggesting that the impact of muscle ischemia on disease progression may vary over time.…”
Section: Functional Muscle Ischemia Due To Loss Of Sarcolemmal Nnosμmentioning
confidence: 99%